Influência de áreas protegidas na qualidade ambiental de áreas alagáveis na Amazônia brasileira - Andrade, Bruna de Souza (Biologia de Água Doce e Pesca Interior - BADPI, 2025)
Aquatic environments worldwide are subject to multiple pressures, leading to a decline in the ecological health of these ecosystems. Protected areas (PAs) have been established to preserve biodiversity and maintain natural ecological processes and ecosystem services. However, the effectiveness of these areas in conserving biological diversity remains under debate. While some studies report positive outcomes of PAs, others highlight the need for adjustments in the protection system to ensure more effective biodiversity conservation. In this context, the objective of this study was to assess environmental quality in floodplain areas of the Amazon under different governance levels, represented by formally protected environments, areas under restricted use (fisheries-managed areas), and unprotected environments. Between 2018 and 2023, we sampled fish in lakes with varying levels of protection and selected nine metrics to construct a fish-based index, the Index of Biotic Integrity for Floodplain Lake (IBI-FL), based on diversity, species composition, trophic categories, and fish abundance. A total of 67,043 individuals were collected, representing 347 species, 46 families, and 14 orders. The results indicated that the biotic integrity of PAs is comparable to that of unprotected areas; however, some individual lakes exhibited good biotic integrity, highlighting the effectiveness of local protection systems. Additionally, we investigated the concentrations of trace metals in different floodplain areas of the Central Amazon, providing reference values for metals in these environments. We collected 43 samples of soil and lake bottom sediments and used inductively coupled plasma optical emission spectrometry (ICP-OES) to determine the concentrations of eleven elements (Al, Ba, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, and Zn). Our findings revealed slight variations in metal concentrations among formally protected, managed, and unprotected areas, reflecting geological contributions and pedogenic processes characteristic of the Amazon region. Therefore, this research fills important gaps in understanding floodplain ecosystem health by providing reference values for trace metals and supporting the development of strategies for environmental quality assessment and pollution control in floodplain areas.
Keywords: Assembleia de peixes; Bioindicadores; Integridade biótica